Small and intermediate strain properties of sands containing fines. Issue 110 (July 2018) - Goudarzy, Meisam; König, Diethard; Schanz, Tom
Abstract: The goal of this paper is to find the influence of fines content, f c, on the fitting parameters of Hardin's relationship to predict shear modulus and damping ratio at small and intermediate shear strain ( G(γ) and η(γ) ). Therefore, a series of resonant column tests were conducted on dry Hostun sand mixed with 0, 5, 10, 20, 30 and 40 % of fines content. Tests were carried out using the resonant column device at Ruhr- Universität Bochum. Experimental data on the adopted material revealed that maximum shear modulus decreases with an increase in f c . Analysis of data showed that fitting parameters of Hardin's relationship must be correlated to f c . In addition, experimental results for an intermediate strain region revealed the significant effect of f c on damping ratio and shear modulus. The results showed that damping ratio increased with fines content up to f c = 20 % and then decreases with further increase of f c . Reference shear strain is a key parameter to describe nonlinear behavior of soils and damping ratio. The analyses of results showed that the reference shear strain decreased with f c up to f c = 20 % and it then increases with further increase of f c for the adopted mixtures. Highlights: A systematic series of resonant column tests were conducted to assess the effect of fines content on shear modulus and damping ratio. The effect of fines content on reference shear strain were assessed. A model was proposed to predict the reference shear strain in sands containing wide range of fines content.